ChemInform Abstract: Enantioselective Fluorination of α‐Chloro‐β‐keto Phosphonates in the Presence of Chiral Palladium Complexes. Issue 41 (19th September 2013) - Woo, Saet Byeol; Suh, Chang Won; Koh, Kwang Oh; Kim, Dae Young
Abstract The optimized conditions include an air‐ and moisture‐stable Pd‐complex.